Biotechnology and genetics in fisheries and aquaculture - Beaumont, A. R. (Andy R.); Boudry, Pierre; Hoare, K. (Chichester ; Ames, Iowa : Blackwell, 2010)
"Following the extremely well-received structure of the first edition, this carefully revised and updated new edition now includes much new information of vital importance to those working and researching in the fisheries and aquaculture industries. Commencing with chapters covering genetic variation and how it can be measured, the authors then look at genetic structure in natural populations, followed by a new chapter covering genetics in relation to population size and conservation issues. Genetic variation of traits and triploids and the manipulation of ploidy are fully covered, and another new chapter is included, entitled F̀rom Genetics to Genomics'. The book concludes with a chapter covering the impact of genetic engineering in aquaculture. With the inclusion of a wealth of up-to-date information, new text and figures and the inclusion of a third author, Pierre Boudry, the second edition of Biotechnology and Genetics in Fisheries and Aqua-culture provides an excellent text and reference of great value and use to upper level students and professionals working across fish biology, aquatic sciences, fisheries, aquaculture, genetics and biotechnology. Libraries in all universities and research establishments where biological sciences, fisheries and aquaculture are studied and taught should have several copies of this excellent new edition on their shelves."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Fishes -- Molecular genetics; Fishes -- Breeding